Investigação de brucelose em pequenos ruminantes - Bombonato, Nadia Grandi (2017)
Over the last decades, sheep and goat farming has undergone technical transformations in the various links of its productive chains. It is an activity explored in all the continents, being exerted in distinct ecosystems with the most different types of climate, soil, topography and vegetation. Due to the importance of this animal’s productions, care for the health of herds must be taken, not only for the loss and damages in the production, but also for the control of diseases that can affect the human being. Among these we have brucellosis, an infectious contagious disease, caused by bacteria of the genus Brucella. Thus, the objective of this research was to investigate the occurrence of brucellosis in two properties of dairy goats and three properties of sheep for meat production in the Alto Paranaíba, MG region. Forty-eight blood samples and lactating goats' milk were collected for the diagnosis of B. abortus, by the Acidified Buffered Antigen (ABT) and Milk Ring Test (MRT). Real-time PCR was also used for the diagnosis of B. abortus and B. melitensis in the milk of these animals. Blood samples were also collected from 30 sheep of three properties in the region, for diagnosis of B. ovis by the IDGA test and real-time PCR. Twenty samples of sheep semen from two Semen Production and Marketing Centers were analyzed by real-time PCR to also verify the presence of B. ovis. For the Ring Test in goat milk, all 48 samples were negative, whereas for the ABT test, a caprine female was positive, showing that B. abortus can also occur in goats. In the diagnosis by real-time PCR, all the milk samples showed negative results for B. abortus and B. melitensis. From 30 sheep blood samples for the IDGA Test, 3 (10%) were positive and confirmed by real-time PCR. Despite the low occurrence of B. abortus, and the non-occurrence of B. melitensis in the goats investigated, there should always be a monitoring of the herds, considering the zoonotic importance of the agents. As for B. ovis, due to the serious problems it causes in sheep breeding, examinations should be done routinely.